PERFORMANCE OF ASPHALT CONCRETE WEARING COURSE (AC-WC) USING BUKIT KUNCIR AGGREGATE AND BATANG HARI AGGREGATE OF WEST SUMATERA - Yuhesdi, Fadly
Road damage will cause in the road role not being implemented according to UU No.38 Tahun 2004. This happened in several regions in Indonesia, one of them is the Province of West Sumatra. Road damage is caused by several factors, one of which is aggregate. There are 2 aggregate sources used, that is Bukit Kuncir aggregate of Solok Regency and Batang Hari aggregate of Dharmasraya Regency. Therefore, it needs to be examined whether the Bukit Kuncir Aggregate and Batang Hari Aggregate meet the requirements in technical specifications and and the performance of the mixture using the aggregate. The method used in this study is an experimental method in the laboratory consisting of aggregate properties testing, asphalt properties testing and AC-WC mixture performance testing, that is resilient modulus testing using Dyamic Testing System and testing the resistance to fatigue cracks using Beam Fatigue Apparatus with control stress. The results of the mixed performance testing will be compared with the Asphalt Institute model. In general, the results of aggregate testing, Bukit Kuncir Aggregate and Batang Hari Aggregate meet the Spesifikasi Umum 2018 Bina requirements and precision requirements. This shows that aggregate is not a factor causing road damage in West Sumatra Province. This statement is supported by the results of mixed performance testing. For AC-WC mixture using Bukit Kuncir Aggregate has resilient modulus value of 5,068,745 MPa and fatigue crack value of 778,432 cycles at a stress 750 kPa and 20 ? temperature and AC-WC mixture using Batang Hari Aggregate has resilient modulus value of 4,490,699 MPa and crack fatigue value of 961,227 cycles at a stress of 500 kPa at a temperature of 20 ?.